Photocatalytic material for degrading dye as well as preparation method and application of photocatalytic material

By growing cuprous oxide and alkaline copper carbonate in situ on the surface of the copper mesh, and combining bismuth oxychloride, Cu2(OH)2CO3/Cu2O@BOC composites were prepared, which solved the problems of low quantum efficiency and difficulty in recycling of existing photocatalysts, and achieved efficient degradation of dyes and environmentally friendly recycling.

CN119633865APending Publication Date: 2025-03-18NANTONG LOVER APPL +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411853916.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing photocatalysts have low quantum efficiency when degrading dyes, there is a distance between catalytic performance and expectations, and it is difficult to recycle and utilize, resulting in secondary pollution in the environment.

Method used

Cu2(OH)2CO3/Cu2O@BOC composite was prepared by growing copper oxide and alkaline copper carbonate in situ on the surface of the copper mesh, combining bismuth oxychloride, and the dispersion and positioning of bismuth oxychloride was promoted using dopamine-modified copper mesh.

Benefits of technology

The catalytic efficiency of photocatalysts is improved, the removal capacity of organic dyes is enhanced, and the recycling of copper nets is simplified, and the material recycling process is reduced and environmental pollution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633865A_ABST
    Figure CN119633865A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a photocatalytic material, which comprises the following steps: adding ferric trichloride into a dopamine aqueous solution to obtain a mixed solution, immersing a copper wire mesh into the mixed solution, keeping the temperature at 30-60 DEG C for 5-30 minutes, adding sodium perborate into the mixed solution, and continuously reacting for 30-60 minutes to obtain a dopamine modified copper wire mesh; adding bismuth oxychloride powder into a hydrochloric acid aqueous solution, and dispersing to obtain a composite solution; the dopamine modified copper mesh is immersed in the composite solution for 10-60 min at the temperature of 25-50 DEG C, and after being taken out, the dopamine modified copper mesh is placed for 10-30 min at the temperature of 25-60 DEG C; and repeating the dipping and standing, and naturally drying at room temperature to obtain the photocatalytic material. According to the preparation method disclosed by the invention, Cu2 (OH) 2CO3 / Cu2O can be generated on the surface of the copper mesh in situ, so that relatively firm combination is formed. The flaky composite material can be simply and conveniently recycled after the dye is degraded, and the prepared composite material has high photocatalytic degradation performance and can be used for removing organic colored pollutants generated in the printing and dyeing industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic degradation, in particular to a method for preparing a photocatalytic material for degrading dyes, a photocatalytic material prepared by the preparation method, and application of the photocatalytic material in degrading dyes. Background Art

[0002] Synthetic dyes are widely used in different industries, such as textiles, leather, food and paper, which inevitably leads to the waste of dyes. At the same time, industrial wastewater generated after industrial production cannot be effectively purified and is generally discharged into the ocean or infiltrated into the soil. Organic dyes such as rhodamine B can cause water coloration, reduce light penetration, and thus interfere with the photosynthesis of aquatic organisms. Due to their complex chemical properties and structures, they are persistent in water dispersion and difficult to be biodegraded. The discharge of these dyes into water bodies is harmful to biodiversity and has a negative impact on human health. Therefore, it is necessary to provide an effective method for removing dyes from the environment.

[0003] In recent years, in response to the national call and green energy conservation and emission reduction, people have conducted extensive research on the removal of organic dyes from wastewater, including photocatalysis, redox degradation, microbial methods, physical adsorption, etc. Compared with other methods, photocatalysis has the advantage of high efficiency. In recent years, photocatalytic research has gradually aroused great interest among researchers, and various semiconductor materials have been used as photocatalysts. However, due to the low quantum efficiency of single-phase photocatalysts, there is still a distance between photocatalytic performance and people's expectations in realization.

[0004] Basic copper carbonate (Cu2(OH)2CO3) and cuprous oxide (Cu2O) are common copper-based Fenton catalysts that can release a large amount of Cu in solution. 2+ and Cu + , is the Cu in the Fenton-like reaction 2+ / Cu + The ion pair cycle provides copper ions. Currently, the methods for preparing Cu2(OH)2CO3 and Cu2O mostly use copper salts as raw materials to react to obtain powder particles, which is difficult to recycle after photocatalysis and easily causes secondary pollution to the environment. The microwave-responsive Bi-based oxide bismuth oxychloride (BiOCl) has a unique layered structure, forming an internal electric field between the layers of the layered structure, but its high recombination rate of photogenerated carriers limits its photocatalytic application.

[0005] For example, Chinese invention patent CN113318759B, a dopamine-mediated bismuth oxychloride photocatalyst and its preparation method and application, provides dopamine-mediated bismuth oxychloride, but it lacks basic copper carbonate and cuprous oxide, and the catalytic efficiency is not high.

[0006] Another example is the Chinese invention patent CN108525702A, a loaded bismuth oxychloride photocatalyst for sewage treatment and its preparation method, which provides a vermiculite clay mineral material, so that the bismuth oxychloride is firmly and evenly loaded thereon, effectively solving the agglomeration problem of bismuth oxychloride. However, vermiculite clay mineral is a powder material, and its recycling is relatively complicated and cannot be promoted and applied.

[0007] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0008] In view of this, in order to overcome the defects of the prior art, the purpose of the present invention is to provide a method for preparing a photocatalytic material for degrading dyes, thereby obtaining a photocatalytic material that uses bismuth oxychloride to promote the in-situ growth of cuprous oxide and basic copper carbonate.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] A method for preparing a photocatalytic material comprises the following steps:

[0011] Adding ferric chloride to a dopamine aqueous solution to obtain a mixed solution, immersing a copper mesh in the mixed solution, maintaining the mixed solution at a temperature of 30-60° C. for 5-30 minutes, adding sodium perborate to the mixed solution, and continuing the reaction for 30-60 minutes to obtain a dopamine-modified copper mesh;

[0012] adding bismuth oxychloride powder into a hydrochloric acid aqueous solution and dispersing the mixture to obtain a composite solution;

[0013] Immersing the dopamine-modified copper mesh in the composite solution at a temperature of 25-50° C. for 10-60 min, taking it out and placing it at 25-60° C. for 10-100 min;

[0014] After repeating the above immersion and placement, the mixture is naturally dried at room temperature to obtain the photocatalytic material.

[0015] According to some preferred embodiments of the present invention, the bismuth oxychloride powder is prepared by the following method:

[0016] Adding sodium citrate and polyvinyl pyrrolidone to the ethanol aqueous solution and mixing to obtain a first solution;

[0017] dissolving bismuth chloride in a mixture of aqueous hydrogen peroxide and hydrochloric acid to obtain a second solution;

[0018] The second solution is added dropwise to the first solution at 60-100° C. After the addition is completed, stirring is continued at 60-100° C. for 1-5 hours to form a precipitate, which is then cooled to room temperature, washed, filtered, and dried to obtain bismuth oxychloride powder.

[0019] According to some preferred implementation aspects of the present invention, the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1-5:1; the concentration of sodium citrate in the first solution is 0.5-5.0 mmol / L; and the concentration of polyvinyl pyrrolidone in the first solution is 0.01-0.5 g / L.

[0020] According to some preferred implementation aspects of the present invention, in the mixed solution consisting of aqueous hydrogen peroxide solution and hydrochloric acid, the concentration of hydrogen peroxide is 1.0-10.0 mmol / L, and the concentration of hydrochloric acid is 1.0-10.0 mmol / L; the concentration of bismuth chloride in the second solution is 0.1-1.0 mol / L.

[0021] According to some preferred embodiments of the present invention, the specification of polyvinyl pyrrolidone is k88-96, and the average molecular weight is 100000-2000000.

[0022] According to some preferred implementation aspects of the present invention, the concentration of the dopamine aqueous solution is 1.0-10.0 mmol / L; the concentration of ferric chloride in the mixed solution is 1.0-1.5 mmol / L.

[0023] According to some preferred embodiments of the present invention, after adding sodium perborate, the concentration of sodium perborate in the mixed solution is 1-5 mmol / L.

[0024] According to some preferred implementation aspects of the present invention, the concentration of bismuth oxychloride in the composite solution is 1.0-5.0 g / L; the dispersion temperature of bismuth oxychloride is 30-60° C., and the dispersion time is 20-40 min.

[0025] The present invention also provides a photocatalytic material prepared according to the above preparation method and the application of the photocatalytic material in degrading dyes, comprising the following steps: placing the photocatalytic material in the dye and irradiating it under ultraviolet light for 5-30 minutes for photocatalytic treatment.

[0026] In some embodiments of the present invention, the concentration of the dye is 20-100 mg / L. The dye is such as rhodamine.

[0027] In some embodiments of the present invention, a method for preparing a photocatalytic material and a method for applying the photocatalytic material to dye degradation include the following steps:

[0028] Step 1: Preparation of bismuth oxychloride (BOC) powder

[0029] Anhydrous ethanol and deionized water are mixed at a volume ratio of 1-5:1, and then sodium citrate and polyvinyl pyrrolidone are added to make the concentration of sodium citrate 0.5-5.0 mmol / L and the concentration of polyvinyl pyrrolidone 0.01-0.5 g / L, and the first solution is obtained after mixing.

[0030] Aqueous hydrogen peroxide solution and hydrochloric acid are mixed to obtain a mixed solution of aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of hydrogen peroxide is 1.0-10.0 mmol / L, and the concentration of hydrochloric acid is 1.0-10.0 mmol / L, and then bismuth chloride is quickly weighed and dissolved in the mixed solution to make the concentration of bismuth chloride 0.1-1.0 mol / L to obtain a second solution.

[0031] At 60-100° C., the second solution is added dropwise to the first solution, and the mixture is continuously stirred at 60-100° C. for 1-5 hours to form a precipitate, then cooled to room temperature, repeatedly washed with a large amount of deionized water, filtered to remove residual unreacted substances and ethanol, and dried to finally obtain bismuth oxychloride (BOC) powder.

[0032] Step 2: Preparation of dopamine-modified copper mesh

[0033] The copper mesh was washed thoroughly with 50-90% ethanol and 1-10 mol / L hydrochloric acid in sequence, and then washed with a large amount of deionized water, and dried to obtain a clean copper mesh.

[0034] A dopamine aqueous solution with a concentration of 1.0-10.0 mmol / L is prepared, and ferric chloride is added to make the concentration of ferric chloride 1.0-1.5 mmol / L to obtain a mixed solution.

[0035] Immerse the clean copper mesh in the mixed solution, raise the temperature to 30-60°C, react for 5-30 minutes, add sodium perborate to a concentration of 1-5mmol / L, continue the reaction for 30-60 minutes, and finally obtain the dopamine-modified copper mesh.

[0036] Step 3: Copper-bismuth synergistic composite photocatalytic material

[0037] The bismuth oxychloride powder is added into a hydrochloric acid aqueous solution with a temperature of 30-60° C. and a concentration of 1-10 mol / L, and stirred to fully disperse the bismuth oxychloride to obtain a composite solution.

[0038] The dopamine-modified copper mesh is immersed in the composite solution at a temperature of 25-50° C. for 10-60 minutes, then taken out and placed at 25-60° C. for 10-100 minutes.

[0039] The copper-bismuth synergistic photocatalytic material is prepared by immersing it in the composite solution again, and the number of repeated immersions is 1 to 9. The copper-bismuth synergistic composite photocatalytic material is finally obtained by natural drying at room temperature.

[0040] Step 4: Degradation of dye

[0041] The prepared copper-bismuth synergistic composite photocatalytic material is placed in a rhodamine B (RhB) solution with a concentration of 20-100 mg / L, and irradiated under ultraviolet light for 5-30 minutes for photocatalytic treatment to degrade the dye.

[0042] The principle of the present invention is that due to the adhesion of polydopamine, bismuth oxychloride is caused to adhere to the surface of the copper mesh during impregnation. Bismuth oxychloride has strong oxidizing properties. During repeated impregnation, the copper mesh is constantly in contact with bismuth oxychloride in the solution and air, thereby generating basic copper carbonate on the surface. At the same time, due to the presence of dilute hydrochloric acid in the solution, part of it will chemically react to generate copper salts and further reduce to cuprous oxide. This is repeated, and eventually cuprous oxide and basic copper carbonate will be in situ grown on the bismuth oxychloride surface of the copper mesh, thereby constructing a copper-bismuth composite catalytic system.

[0043] In-situ catalytic mechanism on the copper mesh surface: Basic copper carbonate (Cu2(OH)2CO3) and cuprous oxide (Cu2O) are common copper-based Fenton catalysts that can release a large amount of Cu in the solution. 2+ and Cu + , is the Cu in the Fenton-like reaction 2+ / Cu + The ion pair cycle provides copper ions. Cuprous oxide itself has photoelectric conversion capability, can absorb visible light, and generate electron-hole pairs. The band gap energy of basic copper carbonate is moderate, and it can absorb light within the visible light range, thereby realizing visible light catalytic reaction. And bismuth oxychloride can form an internal electric field, promote the separation of electron-hole pairs, thereby showing strong photocatalytic activity. In addition, the formation of the basic copper carbonate / cuprous oxide sheet structure increases the contact area between the catalyst and the solution relative to the spherical structure, and also improves the efficiency of the catalysis. Therefore, the present invention obtains a material with higher catalytic efficiency through the synergy of copper and bismuth, and in addition, the catalytic material is generated in situ by bonding dopamine to the copper mesh, so that the recovery of the catalyst can be directly realized by the recovery of the copper mesh. Quick and convenient recycling and reuse.

[0044] Compared with the existing traditional technology, the present invention is beneficial in that:

[0045] 1. According to the preparation method of the present invention, basic copper carbonate / cuprous oxide can be generated in situ on the surface of the copper mesh to form a relatively strong bond, and can still maintain a good content and morphology after washing; after the basic copper carbonate / cuprous oxide flaky composite material degrades the dye, it can be easily recycled through the copper mesh, thereby saving costs and reducing environmental pollution. The prepared composite material can be used to remove organic dyes in the dyeing and finishing industry and chemical pollution.

[0046] 2. By changing the mass of bismuth oxychloride (BOC), different amounts of Cu2(OH)2CO3 / Cu2O can be prepared and Cu2(OH)2CO3 / Cu2O@BOC composite materials can be formed. The doping of Cu2(OH)2CO3 / Cu2O and BOC not only greatly promotes the separation rate of photogenerated carriers and improves the removal efficiency of organic dyes, but also improves the shortcomings of pure powder BOC and Cu2(OH)2CO3 / Cu2O photocatalytic materials that are difficult to recycle, making the photocatalyst have good cycle stability. The Cu2(OH)2CO3 / Cu2O@BOC composite material exhibits excellent photocatalytic performance.

[0047] 3. Bismuth oxychloride, which has a good photocatalytic effect, is used to promote the formation of basic copper carbonate / cuprous oxide, and the Cu2(OH)2CO3 / Cu2O@BOC composite material is prepared quickly and easily. Bismuth oxychloride (BOC) not only plays an important role in the preparation of Cu2(OH)2CO3 / Cu2O of copper mesh-based materials, but also plays a dual photocatalytic role in the photodegradation of organic dyes. The prepared Cu2(OH)2CO3 / Cu2O@BOC composite material can be reused more than ten times. Using BOC to prepare Cu2(OH)2CO3 / Cu2O and simultaneously form Cu2(OH)2CO3 / Cu2O@BOC material is a green, fast and economical way. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0049] Figure 1 The removal performance of RhB dye by Examples 1 to 5 of the present invention is shown.

[0050] Figure 2 The recyclability of RhB dye removed in Example 2 of the present invention.

[0051] Figure 3These are SEM images of (a) BOC, (b) copper mesh, (c) copper mesh@PDA, and (d) Cu2(OH)2CO3 / Cu2O@BOC materials in Example 1 of the present invention (low magnification on the left and high magnification on the right).

[0052] Figure 4 This is the XRD diagram of the Cu2(OH)2CO3 / Cu2O@BOC composite material according to Example 1 of the present invention.

[0053] Figure 5 Embodiment 3 of the present invention ( Figure 5 a) and comparative example 1 ( Figure 5 b) EDX elemental scan of the composite material. DETAILED DESCRIPTION

[0054] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0055] The photocatalytic material for degrading dyes and the preparation method thereof of the present invention avoid the problems of large bandgap of bismuth oxychloride photocatalyst, easy recombination of photogenerated electrons and holes, and inability to recycle the nano copper compound homogeneous catalyst after use. Specifically, the preparation method of the photocatalytic material for degrading dyes of the present invention comprises the following steps:

[0056] Step 1: Preparation of bismuth oxychloride (BOC) powder

[0057] Anhydrous ethanol and deionized water are mixed in a ratio of 1-5:1, and then sodium citrate and polyvinyl pyrrolidone are added to make the concentration of sodium citrate 0.5-5.0 mmol / L and the concentration of polyvinyl pyrrolidone 0.01-0.5 g / L, and the first solution is obtained after stirring and mixing.

[0058] The specification of polyvinyl pyrrolidone is k88-96, the average molecular weight is 100,000-2 million, and the stirring speed is 1000-3000r / min.

[0059] Aqueous hydrogen peroxide solution and hydrochloric acid are mixed in proportion to obtain a mixed solution consisting of aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of hydrogen peroxide is 1.0-10.0 mmol / L, and the concentration of hydrochloric acid is 1.0-10.0 mmol / L, and then bismuth chloride is quickly weighed and dissolved in the mixed solution to make the concentration of bismuth chloride 0.1-1.0 mol / L to obtain a second solution.

[0060] At 60-100° C., the second solution is added dropwise to the first solution, and the mixture is continuously stirred at 60-100° C. for 1-5 hours to form a precipitate, then cooled to room temperature, repeatedly washed with a large amount of deionized water, filtered to remove residual unreacted substances and ethanol, and dried to finally obtain bismuth oxychloride (BOC) powder.

[0061] Step 2: Preparation of dopamine-modified copper mesh

[0062] The copper mesh was washed thoroughly with 50-90% ethanol and 1-10 mol / L hydrochloric acid in sequence, and then washed with a large amount of deionized water, and dried to obtain a clean copper mesh.

[0063] A dopamine aqueous solution with a concentration of 1.0-10.0 mmol / L is prepared, and ferric chloride is added to make the concentration of ferric chloride 1.0-1.5 mmol / L to obtain a mixed solution.

[0064] Immerse the clean copper mesh in the mixed solution, raise the temperature to 30-60°C, react for 5-30 minutes, add sodium perborate to a concentration of 1-5mmol / L, continue the reaction for 30-60 minutes, and finally obtain the dopamine-modified copper mesh.

[0065] Step 3: Copper-bismuth synergistic composite photocatalytic material

[0066] Add BOC powder to a hydrochloric acid aqueous solution at a temperature of 30-60°C and a concentration of 1-10 mol / L, stir to fully disperse bismuth oxychloride, and obtain a composite solution. The concentration of bismuth oxychloride in the composite solution is 1.0-5.0 g / L; the dispersion temperature of bismuth oxychloride is 30-60°C, and the dispersion time is 20-40 minutes.

[0067] The dopamine-modified copper mesh is immersed in the composite solution at a temperature of 25-50° C. for 10-60 minutes, then taken out and placed at 25-60° C. for 10-100 minutes.

[0068] The copper-bismuth synergistic photocatalytic material is prepared by immersing it in the composite solution again, and the number of repeated immersions is 1 to 9. After each immersion, it needs to be taken out and placed, and finally dried naturally at room temperature to finally obtain the copper-bismuth synergistic composite photocatalytic material.

[0069] The copper-bismuth synergistic composite photocatalytic material obtained above is used to degrade dyes, and also includes the following step four.

[0070] Step 4: Degradation of dye

[0071] The prepared copper-bismuth synergistic composite photocatalytic material is placed in a rhodamine B (RhB) solution with a concentration of 20-100 mg / L, and irradiated under ultraviolet light for 5-30 minutes for photocatalytic treatment.

[0072] Embodiment 1

[0073] The preparation method of the photocatalytic material used to degrade dyes in this embodiment is as follows:

[0074] Step 1: Preparation of bismuth oxychloride (BOC)

[0075] Anhydrous ethanol and deionized water were mixed at a volume ratio of 1.2:1, and then 0.082 g of sodium citrate and 0.03 g of polyvinyl pyrrolidone were added, and the mixture was stirred and mixed to obtain a first solution.

[0076] Aqueous hydrogen peroxide solution and hydrochloric acid are mixed in proportion to obtain a mixed solution consisting of aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of hydrogen peroxide is 10 mmol / L, and the concentration of hydrochloric acid is 2.0 mmol / L, and then bismuth chloride is quickly weighed and dissolved in the mixed solution to make the concentration of bismuth chloride 1.0 mol / L, to obtain a second solution.

[0077] When the first solution is heated to 85°C, the second solution is added dropwise to the first solution. The mixed solution is continuously stirred at 85°C for 3 hours to form a precipitate. After the sample is cooled to room temperature, it is repeatedly washed with a large amount of deionized water, the supernatant, residual unreacted substances and ethanol are filtered to remove, and then dried in air at 70°C to obtain BOC powder.

[0078] Step 2: Modify the copper mesh surface using dopamine

[0079] The copper mesh was thoroughly cleaned with 75% ethanol and 2.0 mol / L hydrochloric acid in sequence, then cleaned with a large amount of deionized water, and dried at 60° C. to obtain a clean copper mesh.

[0080] 0.035 g of FeCl3·6H2O was added to a 6.5 mmol / L dopamine aqueous solution to adjust the concentration of ferric chloride to 1.2 mmol / L, thereby obtaining a mixed solution.

[0081] The clean copper mesh was immersed in the mixed solution, the temperature was raised to 50°C, and NaBO3·4H2O was added after 10 minutes to make the concentration of sodium perborate 2mmol / L. The reaction was continued for 50 minutes to finally obtain the copper mesh@PDA modified with dopamine.

[0082] Step 3: Preparation of copper-bismuth synergistic composite photocatalytic material by repeated impregnation method

[0083] 0.1 g of BOC was added to a 10 mol / L hydrochloric acid aqueous solution at a temperature of 30° C. and stirred for 30 min to fully disperse the bismuth oxychloride to obtain a composite solution.

[0084] The copper mesh @PDA with a size of 4×4 cm was immersed in the composite solution at a temperature of 25°C for 60 min, then taken out and placed at 40°C for 15 min. The immersion times were 1 time, and the Cu2(OH)2CO3 / Cu2O@BOC photocatalytic material was finally obtained after natural drying at room temperature.

[0085] Step 4: Degradation of dye

[0086] The prepared photocatalytic material was placed in a RhB solution with a concentration of 100 mg / L, and subjected to photocatalytic treatment by ultraviolet light irradiation for 5-30 minutes.

[0087] Embodiment 2

[0088] The preparation method of the photocatalytic material used to degrade dyes in this embodiment is as follows:

[0089] Step 1: Preparation of bismuth oxychloride (BOC)

[0090] Anhydrous ethanol and deionized water were mixed at a volume ratio of 1.2:1, and then 0.082 g of sodium citrate and 0.03 g of polyvinyl pyrrolidone were added, and the mixture was stirred and mixed to obtain a first solution.

[0091] The mixture is mixed according to a proportion to obtain a mixture consisting of an aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of the hydrogen peroxide is 5.0 mmol / L, and the concentration of the hydrochloric acid is 1.0 mmol / L. Subsequently, bismuth chloride is quickly weighed and dissolved in the above-mentioned mixed solution to make the concentration of bismuth chloride 0.5 mol / L, thereby obtaining a second solution.

[0092] When the first solution is heated to 85°C, the second solution is added dropwise to the first solution. The mixture is stirred continuously at 85°C for 3 hours. After the sample is cooled to room temperature, it is repeatedly washed with a large amount of deionized water, the supernatant, residual unreacted substances and ethanol are filtered to remove the supernatant, and the mixture is dried in air at 70°C to finally obtain BOC powder.

[0093] Step 2: Modify the copper mesh surface using dopamine

[0094] The copper mesh was thoroughly cleaned with 75% ethanol and 2.0 mol / L hydrochloric acid in sequence, then cleaned with a large amount of deionized water, and dried at 60° C. to obtain a clean copper mesh.

[0095] 0.035 g of FeCl3·6H2O was added to a 6.5 mmol / L dopamine aqueous solution to adjust the concentration of ferric chloride to 1.2 mmol / L, thereby obtaining a mixed solution.

[0096] The clean copper mesh was immersed in the mixed solution, the temperature was raised to 50°C, and NaBO3·4H2O was added after 10 minutes to make the concentration of sodium perborate 2mmol / L. The reaction was continued for 50 minutes to finally obtain the copper mesh@PDA modified with dopamine.

[0097] Step 3: Preparation of copper-bismuth synergistic composite photocatalytic material by repeated impregnation method

[0098] 0.2 g of BOC was added to a hydrochloric acid aqueous solution at a temperature of 40° C. and a concentration of 8 mol / L, and stirred for 30 minutes to fully disperse the bismuth oxychloride to obtain a composite solution.

[0099] The 4×4 cm copper mesh @PDA was immersed in the composite solution at 50°C for 10 min, then taken out and placed at 25°C for 30 min. The above immersion and placement were repeated for a total of 3 times, and then dried naturally at room temperature to finally obtain the copper-bismuth synergistic photocatalytic material Cu2(OH)2CO3 / Cu2O@BOC.

[0100] Embodiment 3

[0101] The preparation method of the photocatalytic material used to degrade dyes in this embodiment is as follows:

[0102] Step 1: Preparation of bismuth oxychloride (BOC)

[0103] Anhydrous ethanol and deionized water were mixed at a volume ratio of 1.2:1, and then 0.082 g of sodium citrate and 0.03 g of polyvinyl pyrrolidone were added, and the mixture was stirred and mixed to obtain a first solution.

[0104] Aqueous hydrogen peroxide solution and hydrochloric acid are mixed in proportion to obtain a mixed solution consisting of aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of hydrogen peroxide is 10.0 mmol / L, and the concentration of hydrochloric acid is 1.0 mmol / L, and then bismuth chloride is quickly weighed and dissolved in the mixed solution to make the concentration of bismuth chloride 0.2 mol / L, to obtain a second solution.

[0105] When the first solution was heated to 85°C, the second solution was added dropwise to the first solution. The mixture was stirred continuously at 85°C for 3 hours. After the sample was cooled to room temperature, it was repeatedly washed with a large amount of deionized water. The supernatant, residual unreacted substances and ethanol were filtered to remove the supernatant, and the mixture was dried in air at 70°C to finally obtain BOC powder.

[0106] Step 2: Modify the copper mesh surface using dopamine

[0107] The copper mesh was thoroughly cleaned with 75% ethanol and 2.0 mol / L hydrochloric acid in sequence, then cleaned with a large amount of deionized water, and dried at 60° C. to obtain a clean copper mesh.

[0108] 0.035 g of FeCl3·6H2O was added to a 6.5 mmol / L dopamine aqueous solution to adjust the concentration of ferric chloride to 1.2 mmol / L, thereby obtaining a mixed solution.

[0109] The clean copper mesh was immersed in the mixed solution, the temperature was raised to 50°C, and NaBO3·4H2O was added after 10 minutes to make the concentration of sodium perborate 2mmol / L. The reaction was continued for 50 minutes to finally obtain the copper mesh@PDA modified with dopamine.

[0110] Step 3: Preparation of copper-bismuth synergistic composite photocatalytic material by repeated impregnation method

[0111] 0.3 g of BOC was added to a 5 mol / L hydrochloric acid aqueous solution at a temperature of 50° C. and stirred for 30 min to fully disperse the bismuth oxychloride to obtain a composite solution.

[0112] The copper mesh @PDA with a size of 4×4 cm was immersed in the composite solution at a temperature of 30°C for 30 min, then taken out and placed at 30°C for 20 min. The above immersion and placement were repeated for a total of 5 times, and then dried naturally at room temperature to finally obtain the Cu2(OH)2CO3 / Cu2O@BOC photocatalytic material.

[0113] Embodiment 4

[0114] The preparation method of the photocatalytic material used to degrade dyes in this embodiment is as follows:

[0115] Step 1: Preparation of bismuth oxychloride (BOC)

[0116] Anhydrous ethanol and deionized water were mixed at a volume ratio of 1.2:1, and then 0.082 g of sodium citrate and 0.03 g of polyvinyl pyrrolidone were added, and the mixture was stirred and mixed to obtain a first solution.

[0117] Aqueous hydrogen peroxide solution and hydrochloric acid are mixed in proportion to obtain a mixed solution consisting of aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of hydrogen peroxide is 8.0 mmol / L, and the concentration of hydrochloric acid is 2.0 mmol / L, and then bismuth chloride is quickly weighed and dissolved in the mixed solution to make the concentration of bismuth chloride 0.4 mol / L, to obtain a second solution.

[0118] When the first solution was heated to 85°C, the second solution was added dropwise to the first solution. The mixture was stirred continuously at 85°C for 3 hours. After the sample was cooled to room temperature, it was repeatedly washed with a large amount of deionized water. The supernatant, residual unreacted substances and ethanol were filtered to remove the supernatant, and the mixture was dried in air at 70°C to finally obtain BOC powder.

[0119] Step 2: Modify the copper mesh surface using dopamine

[0120] The copper mesh was thoroughly cleaned with 75% ethanol and 2.0 mol / L hydrochloric acid in sequence, then cleaned with a large amount of deionized water, and dried at 60° C. to obtain a clean copper mesh.

[0121] 0.035 g of FeCl3·6H2O was added to a 6.5 mmol / L dopamine aqueous solution to adjust the concentration of ferric chloride to 1.2 mmol / L, thereby obtaining a mixed solution.

[0122] The clean copper mesh was immersed in the mixed solution, the temperature was raised to 50°C, and NaBO3·4H2O was added after 10 minutes to make the concentration of sodium perborate 2mmol / L. The reaction was continued for 50 minutes to finally obtain the copper mesh@PDA modified with dopamine.

[0123] Step 3: Preparation of copper-bismuth synergistic composite photocatalytic material by repeated impregnation method

[0124] 0.4 g of BOC was added to a 2 mol / L hydrochloric acid aqueous solution at 60° C. and stirred for 30 min to fully disperse the bismuth oxychloride to obtain a composite solution.

[0125] The copper mesh @PDA with a size of 4×4 cm was immersed in the composite solution at a temperature of 40°C for 20 min, then taken out and placed at 30°C for 25 min. The above immersion and placement were repeated for a total of 7 times, and then dried naturally at room temperature to finally obtain the Cu2(OH)2CO3 / Cu2O@BOC photocatalytic material.

[0126] Embodiment 5

[0127] The preparation method of the photocatalytic material used to degrade dyes in this embodiment is as follows:

[0128] Step 1: Preparation of bismuth oxychloride (BOC)

[0129] Anhydrous ethanol and deionized water were mixed at a volume ratio of 1.2:1, and then 0.082 g of sodium citrate and 0.03 g of polyvinyl pyrrolidone were added, and the mixture was stirred and mixed to obtain a first solution.

[0130] Aqueous hydrogen peroxide solution and hydrochloric acid are mixed in proportion to obtain a mixed solution consisting of aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of hydrogen peroxide is 5.0 mmol / L, and the concentration of hydrochloric acid is 5.0 mmol / L, and then bismuth chloride is quickly weighed and dissolved in the mixed solution to make the concentration of bismuth chloride 0.2 mol / L, to obtain a second solution.

[0131] When the first solution was heated to 85°C, the second solution was added dropwise to the first solution. The mixture was stirred continuously at 85°C for 3 hours. After the sample was cooled to room temperature, it was repeatedly washed with a large amount of deionized water. The supernatant, residual unreacted substances and ethanol were filtered to remove the supernatant, and the mixture was dried in air at 70°C to finally obtain BOC powder.

[0132] Step 2: Modify the copper mesh surface using dopamine

[0133] The copper mesh was thoroughly cleaned with 75% ethanol and 2.0 mol / L hydrochloric acid in sequence, then cleaned with a large amount of deionized water, and dried at 60° C. to obtain a clean copper mesh.

[0134] 0.035 g of FeCl3·6H2O was added to a 6.5 mmol / L dopamine aqueous solution to adjust the concentration of ferric chloride to 1.2 mmol / L, thereby obtaining a mixed solution.

[0135] The clean copper mesh was immersed in the mixed solution, the temperature was raised to 50°C, and NaBO3·4H2O was added after 10 minutes to make the concentration of sodium perborate 2mmol / L. The reaction was continued for 50 minutes to finally obtain the copper mesh@PDA modified with dopamine.

[0136] Step 3: Preparation of copper-bismuth synergistic composite photocatalytic material by repeated impregnation method

[0137] 0.5 g of BOC was added to a 4 mol / L hydrochloric acid aqueous solution at a temperature of 60° C. and stirred for 30 min to fully disperse the bismuth oxychloride to obtain a composite solution.

[0138] The copper mesh @PDA with a size of 4×4 cm was immersed in the composite solution at a temperature of 25°C for 60 min, then taken out and placed at 60°C for 20 min. The above immersion and placement were repeated for a total of 9 times, and then dried naturally at room temperature to finally obtain the Cu2(OH)2CO3 / Cu2O@BOC photocatalytic material.

[0139] Comparative Example 1

[0140] The photocatalytic material in this comparative example is not modified by dopamine, and its preparation method is as follows:

[0141] Step 1: Preparation of bismuth oxychloride (BOC)

[0142] Anhydrous ethanol and deionized water were mixed at a volume ratio of 1.2:1, and then 0.082 g of sodium citrate and 0.03 g of polyvinyl pyrrolidone were added, and the mixture was stirred and mixed to obtain a first solution.

[0143] The mixture is mixed according to a proportion to obtain a mixture consisting of an aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of the hydrogen peroxide is 10 mmol / L, and the concentration of the hydrochloric acid is 1.0 mmol / L. Subsequently, bismuth chloride is quickly weighed and dissolved in the above-mentioned mixed solution to make the concentration of bismuth chloride 0.2 mol / L, thereby obtaining a second solution.

[0144] When the first solution is heated to 85°C, the second solution is added dropwise to the first solution. The mixture is stirred continuously at 85°C for 3 hours. After the sample is cooled to room temperature, it is repeatedly washed with a large amount of deionized water, the supernatant, residual unreacted substances and ethanol are filtered to remove the supernatant, and the mixture is dried in air at 70°C to finally obtain BOC powder.

[0145] Step 2: Preparation of clean copper mesh

[0146] The copper mesh was thoroughly cleaned with 75% ethanol and 2.0 mol / L hydrochloric acid in sequence, then cleaned with a large amount of deionized water, and dried at 60° C. for later use.

[0147] Step 3: Preparation of copper-bismuth synergistic composite photocatalytic material by repeated impregnation method

[0148] 0.3 g of BOC was added to a 5 mol / L hydrochloric acid aqueous solution at a temperature of 50° C. and stirred for 30 min to fully disperse the bismuth oxychloride to obtain a composite solution.

[0149] A 4×4 cm copper mesh @PDA was immersed in the composite solution at 30°C for 30 min, then taken out and placed at 30°C for 20 min. The above immersion and placement were repeated for a total of 5 times, and the composite photocatalytic material was finally obtained by natural drying at room temperature.

[0150] Comparative Example 2

[0151] The third step of the photocatalytic material preparation method in this comparative example is only a single dipping, without repeated dipping and placement. The specific preparation method is as follows:

[0152] Step 1: Preparation of bismuth oxychloride (BOC)

[0153] Anhydrous ethanol and deionized water were mixed at a volume ratio of 1.2:1, and then 0.082 g of sodium citrate and 0.03 g of polyvinyl pyrrolidone were added, and the mixture was stirred and mixed to obtain a first solution.

[0154] The mixture is mixed according to a proportion to obtain a mixture consisting of an aqueous hydrogen peroxide solution and hydrochloric acid, wherein the concentration of the hydrogen peroxide is 5.0 mmol / L, and the concentration of the hydrochloric acid is 1.0 mmol / L. Subsequently, bismuth chloride is quickly weighed and dissolved in the above-mentioned mixed solution to make the concentration of bismuth chloride 0.5 mol / L, thereby obtaining a second solution.

[0155] When the first solution is heated to 85°C, the second solution is added dropwise to the first solution. The mixture is stirred continuously at 85°C for 3 hours. After the sample is cooled to room temperature, it is repeatedly washed with a large amount of deionized water, the supernatant, residual unreacted substances and ethanol are filtered to remove the supernatant, and the mixture is dried in air at 70°C to finally obtain BOC powder.

[0156] Step 2: Modify the copper mesh surface using dopamine

[0157] The copper mesh was thoroughly cleaned with 75% ethanol and 2.0 mol / L hydrochloric acid in sequence, then cleaned with a large amount of deionized water, and dried at 60° C. to obtain a clean copper mesh.

[0158] 0.035 g of FeCl3·6H2O was added to a 6.5 mmol / L dopamine aqueous solution to adjust the concentration of ferric chloride to 1.2 mmol / L, thereby obtaining a mixed solution.

[0159] The clean copper mesh was immersed in the mixed solution, the temperature was raised to 50°C, and NaBO3·4H2O was added after 10 minutes to make the concentration of sodium perborate 2mmol / L. The reaction was continued for 50 minutes to finally obtain the copper mesh@PDA modified with dopamine.

[0160] Step 3: Preparation of copper-bismuth synergistic composite photocatalytic material by single impregnation

[0161] 0.2 g of BOC was added to a hydrochloric acid aqueous solution at a temperature of 40° C. and a concentration of 8 mol / L, and stirred for 30 minutes to fully disperse the bismuth oxychloride to obtain a composite solution.

[0162] A 4×4 cm copper mesh @PDA was immersed in the composite solution at a temperature of 50° C. for 10 min, then taken out and naturally dried at room temperature to finally obtain a photocatalytic material.

[0163] Tests and Results

[0164] (1) The materials BOC, copper mesh, copper mesh@PDA, and Cu2(OH)2CO3 / Cu2O@BOC prepared in the above examples and comparative examples were analyzed by SEM, XRD and other characterization techniques for surface morphology, crystal structure and catalytic activity. The photocatalytic activity and recycling stability of the prepared Cu2(OH)2CO3 / Cu2O@BOC were evaluated by degrading RhB in water.

[0165] Depend on Figure 3 The SEM image of (a) shows that the pure BOC structure is spherical and has uniform layers. Figure 3 (c) It can be seen that the surface of the treated copper mesh presents different structures, and the particles are flaky and evenly distributed. Figure 3 (d) It can be clearly seen that Cu2(OH)2CO3 / Cu2O@BOC is evenly distributed on the surface of the copper mesh, forming a lamellar structure.

[0166] The crystal structure was studied by XRD analysis. Figure 4 As shown, it is shown that the characteristic peaks of Cu2(OH)2CO3, Cu2O and BOC are retained in the Cu2(OH)2CO3 / Cu2O@BOC composite material prepared in Example 1, proving the successful preparation of Cu2(OH)2CO3 / Cu2O@BOC.

[0167] EDX element scanning ( Figure 5 ) It can be seen that the elements Cu, O, C, Bi, Cl, and N appear in the Cu2(OH)2CO3 / Cu2O@BOC prepared in Example 3, proving the successful introduction of BOC. At the same time, in order to eliminate the influence of PDA, the photocatalytic material without PDA modification under the same conditions was prepared in Comparative Example 1. After EDX element scanning, it was found that the element C also appeared. It was judged that the introduction of the element C was due to the generation of Cu2(OH)2CO3, proving the successful preparation of Cu2(OH)2CO3.

[0168] (2) Photocatalytic performance

[0169] Photocatalytic performance of the example materials

[0170] In order to evaluate the photocatalytic performance of the samples prepared in the example, 50 mg / L of RhB was degraded under ultraviolet light. After 5 min of illumination, Figure 1 As shown, the degradation rates of RhB of the composite materials prepared in Examples 1 to 5 reached 89%, 99%, 98%, 98% and 98%, respectively.

[0171] After 10 cycles of testing ( Figure 2 ), the photocatalytic performance did not decrease significantly, only decreased by 15%, indicating that the addition of dopamine makes the photocatalytic material strongly bonded to the copper mesh, not easy to fall off, and can be reused. This shows that the Cu2(OH)2CO3 / Cu2O@BOC composite material not only significantly improves the photocatalytic activity, but also effectively improves the problem of difficult recycling of BOC.

[0172] Photocatalytic performance of comparative materials

[0173] In order to evaluate the photocatalytic performance of the samples prepared in the comparative example, 20 mg / L of RhB was degraded under ultraviolet light. After 10 minutes of illumination, the degradation rate of RhB of the sample prepared in comparative example 1 without dopamine treatment was 82%, and after one cycle test, the photocatalytic performance decreased significantly, and the degradation rate of RhB was only 65%, which further demonstrated that dopamine enhanced the bonding between the photocatalytic material and the copper mesh; the degradation rate of RhB of the sample prepared in comparative example 2 was only 58%, which further proved that the photocatalytic composite material Cu2(OH)2CO3 / Cu2O@BOC prepared in the example had good photocatalytic activity.

[0174] In summary, the Cu2(OH)2CO3 / Cu2O@BOC composite material prepared in the embodiment not only greatly promotes the separation rate of photogenerated carriers and improves the removal efficiency of RhB, but also improves the problem of difficult recovery of BOC, making the photocatalyst have good cycle stability. Therefore, the BiOCl-modified copper mesh with both photocatalytic and oxidative properties is prepared by using BOC, and basic copper carbonate / cuprous oxide is grown in situ to prepare the Cu2(OH)2CO3 / Cu2O@BOC composite material, thereby obtaining excellent photocatalytic performance and effective material recovery.

[0175] The photocatalytic material for degrading dyes and the preparation method thereof of the present invention comprise the following steps: adding sodium citrate and polyvinyl pyrrolidone to a solution mixed with hydrogen peroxide and hydrochloric acid, heating the solution at 85°C for 3 hours, washing the solution to obtain bismuth oxychloride (BOC); then adding the BOC and the cleaned copper mesh to dilute hydrochloric acid for repeated immersion, and drying the solution to obtain a sheet-like composite material with different generated amounts: Cu2(OH)2CO3 / Cu2O@BOC (basic copper carbonate / cuprous oxide containing bismuth oxychloride). Using the photocatalytic composite material prepared by the present invention, Cu2(OH)2CO3 / Cu2O@BOC can be generated in situ on the surface of the copper mesh to form a relatively firm bond. After the sheet-like composite material degrades the dye, it can be easily recycled to increase the efficiency of repeated use, thereby saving costs and reducing environmental pollution. The prepared composite material has a strong photocatalytic degradation performance and can be used to remove organic colored pollutants generated in the printing and dyeing industry.

[0176] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a photocatalytic material for degrading dyes, characterized in that: The steps include: Adding ferric chloride to a dopamine aqueous solution to obtain a mixed solution, immersing a copper mesh in the mixed solution, maintaining the mixed solution at a temperature of 30-60° C. for 5-30 minutes, adding sodium perborate to the mixed solution to make the concentration of sodium perborate in the mixed solution 1-5 mmol / L, and continuing the reaction for 30-60 minutes to obtain a dopamine-modified copper mesh; The bismuth oxychloride powder is added into a hydrochloric acid aqueous solution having a temperature of 30-60° C. and a concentration of 1-10 mol / L, and dispersed to obtain a composite solution; Immersing the dopamine-modified copper mesh in the composite solution at a temperature of 25-50° C. for 10-60 min, taking it out and placing it at 25-60° C. for 10-100 min; After repeating the above immersion and placement, the mixture is naturally dried at room temperature to obtain the photocatalytic material.

2. The preparation method according to any one of claim 1, characterized in that: The concentration of the dopamine aqueous solution is 1.0-10.0 mmol / L; the concentration of ferric chloride in the mixed solution is 1.0-1.5 mmol / L.

3. The preparation method according to claim 1, characterized in that: The dispersion time is 20-40 minutes, and the concentration of bismuth oxychloride in the composite solution is 1.0-5.0 g / L.

4. The preparation method according to claim 1, characterized in that: The bismuth oxychloride powder is prepared by the following method: Adding sodium citrate and polyvinyl pyrrolidone to the ethanol aqueous solution and mixing to obtain a first solution; dissolving bismuth chloride in a mixture of aqueous hydrogen peroxide and hydrochloric acid to obtain a second solution; The second solution is added dropwise to the first solution at 60-100° C. After the addition is completed, stirring is continued at 60-100° C. for 1-5 hours to form a precipitate, which is then cooled to room temperature, washed, filtered, and dried to obtain bismuth oxychloride powder.

5. The preparation method according to claim 4, characterized in that: The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1-5:1; the concentration of sodium citrate in the first solution is 0.5-5.0 mmol / L; and the concentration of polyvinyl pyrrolidone in the first solution is 0.01-0.5 g / L.

6. The preparation method according to claim 4, characterized in that: In the mixed solution consisting of the aqueous hydrogen peroxide solution and hydrochloric acid, the concentration of hydrogen peroxide is 1.0-10.0 mmol / L, and the concentration of hydrochloric acid is 1.0-10.0 mmol / L; the concentration of bismuth chloride in the second solution is 0.1-1.0 mol / L.

7. The preparation method according to claim 4, characterized in that: The specification of the polyvinyl pyrrolidone is k88-96, and the average molecular weight is 100000-2000000.

8. A photocatalytic material prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the photocatalytic material as claimed in claim 8 for degrading dyes, characterized in that: The method comprises the following steps: placing the photocatalytic material in dye and irradiating the dye under ultraviolet light for 5-30 minutes to perform photocatalytic treatment.

Citation Information

Patent Citations

  • Supported-type bismuth oxychloride photocatalyst for wastewater treatment and preparation method of supported-type bismuth oxychloride photocatalyst

    CN108525702A

  • A dopamine-mediated bismuth oxychloride photocatalyst, its preparation method and application

    CN113318759B